INTRAOPERATIVE FLUORESCENCE-GUIDED NEUROSURGERY: ADVANCING PRECISION AND RESECTION OUTCOMES IN MALIGNANT BRAIN TUMORS (Global Conference on Medical and Health Sciences, 2026)
Intraoperative fluorescence-guided surgery (FGS) has emerged as a transformative technique in neurosurgical oncology, enabling enhanced visualization of tumor margins during resection of malignant brain tumors. By utilizing fluorescent agents such as 5-aminolevulinic acid (5-ALA) and fluorescein sodium, FGS allows real-time differentiation between tumor tissue and surrounding healthy brain structures, thereby improving surgical precision and clinical outcomes.
Keywords: Fluorescence-guided surgery; Neurosurgery; Brain tumors; 5-ALA; Fluorescein; Tumor resection; Intraoperative imaging; Neuro-oncology; Surgical precision; Glioma